CAMPYLOBACTER SP. IN FECES OF MARSH DEER (BLASTOCERUS DICHOTOMUS) - Giuffrida, R. [UNESP] (2024)
Campylobacter spp. was studied in feces samples from 74 marsh deer (Blastocerus dichotomus) from the western part of central Brazil, using direct growth in Butzler medium and filtration techniques. No strain species were isolated; these findings are discussed.